1995
DOI: 10.1021/bi00003a040
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Human Calcitonin and Glucagon Receptors Reveal Two Dissociable Calcitonin Interaction Sites

Abstract: Two chimeric receptors were constructed by transposing the coding regions for the putative N-terminal domains of the human calcitonin (hCTR) and glucagon (hGGR) receptors. These receptors were stably expressed as glycosylated proteins with molecular masses of 80 kDa for the calcitonin receptor N-terminus chimera (NtCTr) and 65 kDa for the glucagon receptor N-terminus chimera (NtGGr). The NtCTr chimera binds salmon calcitonin (sCT) with an apparent Kd of 12 nM relative to 0.3 nM for the native hCTR. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
92
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 21 publications
7
92
0
Order By: Relevance
“…However, the molecular mechanism of ligand binding of CT to its receptor is not well understood. The amino terminus of the CT receptor has been shown to be critical in ligand binding by mutagenesis (11)(12)(13) and recently by photoaffinity labeling (20,21). The current report continues to use the photoaffinity labeling approach and shows that a amino-terminal photolabile CT agonist probe labels a receptor residue (Leu 368 ) in the third extracellular loop domain, a region distinct from the region that had been labeled by previous calcitonin probes (20,21).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…However, the molecular mechanism of ligand binding of CT to its receptor is not well understood. The amino terminus of the CT receptor has been shown to be critical in ligand binding by mutagenesis (11)(12)(13) and recently by photoaffinity labeling (20,21). The current report continues to use the photoaffinity labeling approach and shows that a amino-terminal photolabile CT agonist probe labels a receptor residue (Leu 368 ) in the third extracellular loop domain, a region distinct from the region that had been labeled by previous calcitonin probes (20,21).…”
Section: Resultsmentioning
confidence: 77%
“…Class B receptors have distinct signature sequences, including a long complex amino-terminal domain with six conserved cysteine residues that are believed to be involved in intradomain disulfide bonds critical for establishing functional receptor conformation (6 -10). Members included in this family are receptors for moderately large peptides having diffuse pharmacophoric domains, such as secretin, calcitonin, glucagon, vasoactive intestinal polypeptide, pituitary adenylate cyclase-activating polypeptide, and parathyroid hormone, sharing 30 to 50% homology with each other.The unique amino-terminal domain of the CT receptor has been shown to be critical for agonist binding and receptor activation using chimeric receptor studies (11)(12)(13). This represents a consistent theme for other class B family members (14 -19).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Crystals of the purified MBP-PTH1R-ECD bound to a synthetic PTH fragment (residues [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were grown in hanging drops containing a reservoir solution of 100 mM sodium cacodylate (pH 6.5) and 30% (vol/vol) polypropylene glycol P400 (PPG P400). Diffraction data were collected at 21-ID-D (LS-CAT) of the Advanced Photon Source at Argonne National Laboratory (Argonne, IL).…”
Section: Methodsmentioning
confidence: 99%
“…The C-terminal fragment of PTH (residues 15-34) binds to the N-terminal ECD of the receptor to confer high affinity and specificity to the receptor (28,29). This ''two-domain'' model of PTH binding and activation is further supported by studies with chimeric ligands and receptors (30)(31)(32) and has since been demonstrated for other class B GPCR molecules (33)(34)(35).…”
mentioning
confidence: 88%